2001
DOI: 10.1007/s004250000436
|View full text |Cite
|
Sign up to set email alerts
|

Stored cysteine proteinases start globulin mobilization in protein bodies of embryonic axes and cotyledons during vetch ( Vicia sativa L.) seed germination

Abstract: Inhibition of protein synthesis by cycloheximide during vetch seed germination, did not prevent globulin breakdown as indicated by a decrease in vicilin- and legumin-specific immunosignals on Western blots. Protein bodies isolated from embryo axes and cotyledons of dry vetch (Vicia sativa L.) seeds using a non-aqueous method were found to be free of cytoplasmic and organellar contaminations. Lysates of these purified protein bodies were capable of degrading globulins; this process was blocked by the cysteine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…Protein bodies of seeds contain both storage proteins and protease precursors. The latter become activated after germination and start degradation of the stored proteins [6]. The activities of cysteine proteinases respond dramatically to different internal and external stimuli and in some cases they rise to 90% of total proteolytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Protein bodies of seeds contain both storage proteins and protease precursors. The latter become activated after germination and start degradation of the stored proteins [6]. The activities of cysteine proteinases respond dramatically to different internal and external stimuli and in some cases they rise to 90% of total proteolytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…These changes have been documented by following globulin mobilization using both histological stains and immunohistochemical analyses (Hö glund et al, 1992;Tiedemann et al, 2000). For example, in vetch (Vicia sativa), the first storage proteins to be mobilized, 2 to 3 d post germination, are those located in embryo axis cells; mobilization of the globulins stored in the cotyledons typically starts thereafter (Schlereth et al, 2000;Tiedemann et al, 2000). Further studies have shown that the sites of mobilization of the protein reserves coincide with the sites of growth and differentiation in the embryonic axes, such as in the radicles, where globulin breakdown starts in the epidermis and prevascular strands and then proceeds toward the embryonic shoot.…”
mentioning
confidence: 99%
“…Papain-like cysteine protease such as CPR2 and CPR4 are found in cotyledon and axis of dry and imbibed seeds. Gene expression studies concluded that storage globulin mobilization in germinating vetch seeds is started by the stored cysteine proteases (CPRs), however, the bulk globulin mobilization is mediated by de novo synthesized CPRs (Schlereth et al, 2000;Schlereth et al, 2001;Tiedemann et al, 2001). These data suggest that papain-like cysteine proteases may play physiological roles and functions in association with seed storage globulin protein degradation and mobilization during seed germination and seedling growth.…”
Section: Association Of Vacuolar Processing Enzyme and Papain-like Cymentioning
confidence: 99%
“…However, sweet potato SPAE is in close association with plant vacuolar processing enzymes of seeds from phylogenetic analysis (Chen et al, 2004). Vacuolar processing enzymes have been reported to be in association with the degradation and mobilization of globulin storage proteins during seed germination and seedling growth in Phaseolus vulgaris (Senyuk et al, 1998), Vigna mungo , Vicia sativa (Schlereth et al, 2000;Schlereth et al, 2001), and Arabidopsis thaliana (Gruis et al, 2002). In Vigna mungo, VmPE-1 has been demonstrated to increase in the cotyledons of germinating seeds and was involved in the post-translational processing of a vacuolar cysteine endopeptidase, designated SH-EP, which degraded seed storage proteins (Okamoto & www.intechopen.com Transgenic Plants -Advances and Limitations 244 Minamikawa, 1999).…”
Section: Expression Of Sweet Potato Asparaginyl Endopeptidase Spae Almentioning
confidence: 99%
See 1 more Smart Citation